2011
DOI: 10.2298/soc1102149b
|View full text |Cite
|
Sign up to set email alerts
|

Second demographic transition de-blocked?

Abstract: The text is re-examining the previously established dilemma related to whether Serbia (without Kosovo and Metohija) is the country of second demographic transition, i.e.: has the transition been de-blocked, under the assumption that this is a worldwide historical process of transformation of industrialized countries. The last thesis, around which there exists a lot of controversy in the contemporary population theory, is however not dealt with in detail; to the contrary, it is used as the general theoret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 3 publications
0
16
0
5
Order By: Relevance
“…e Serbian rural population is characterised by some features of the second demographic transition (continued decrease in birth rate, postponement of marriage, decline in nuptiality rate, growth of divorce rate). Nevertheless, in making the nal conclusion about this process we should be very careful because studies showed very slow ideational change in our society (Bobić, Vukelić 2011). At the same time, the researchers pointed out that the families and households remain the main generators of patriarchal orientation (Bobić, Vukelić 2011;Pešić 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…e Serbian rural population is characterised by some features of the second demographic transition (continued decrease in birth rate, postponement of marriage, decline in nuptiality rate, growth of divorce rate). Nevertheless, in making the nal conclusion about this process we should be very careful because studies showed very slow ideational change in our society (Bobić, Vukelić 2011). At the same time, the researchers pointed out that the families and households remain the main generators of patriarchal orientation (Bobić, Vukelić 2011;Pešić 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, in making the nal conclusion about this process we should be very careful because studies showed very slow ideational change in our society (Bobić, Vukelić 2011). At the same time, the researchers pointed out that the families and households remain the main generators of patriarchal orientation (Bobić, Vukelić 2011;Pešić 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Strategies for overcoming structural risks on an individual level are seen primarily as strategies for adapting the existing models of marriage and family, emphasizing that widespread deprivation, both at the higher and lower social strata, is reflected in the greater representation of cohabitation and nonmarital childbearing among people at the bottom of the social ladder (Petrović, 2011). The authors who sought to evaluate the applicability of the second demographic transition theory to processes in Serbia, analyzing the characteristics of marital behavior in terms of marriage, divorce, and fertility traits, (Bobić, Vukelić, 2011) conclude that it is difficult to give a clear and precise answer based on existing insights and that further research is needed. When it comes to childbearing, they associate it with the conditions of post-socialist transition, emphasizing that mothers who give birth outside of marriage (primarily young) are at high risk of poverty, unemployment, reduced chances for education, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Стратегије превазилажења структурних ризика на индивидуалном плану сагледавају се пре свега као стратегије адаптације постојећих модела брачности и породице, уз нагласак да се широко присутна депривација, како код виших, тако и код нижих социјалних слојева, огледа и у већој заступљености кохабитација и рађања ван брака међу становништвом на доњем делу социјалне лествице (Petrović, 2011). Аутори који су настојали да оцене применљивост теорије друге демографске транзиције на процесе у Србији, анализирајући карактеристике брачног понашања становништва у вези са склапањем брака, разводима и одликама фертилитета (Bobić, Vukelić, 2011), закључују да је на основу постојећих увида тешко дати јасан и прецизан одговор, и да су неопходна додатна истраживања. Када је реч о рађању ван брака, повезују га са условима постсоцијалистичке транзиције, наглашавајући да су мајке које рађају ван брака (пре свега младе) изложене великим ризицима од сиромаштва, незапослености, смањених шанси за образовање итд.…”
unclassified
“…In a growing number of post-socialist countries, the period after 1990 is considered from the perspective of the second demographic transition (Sobotka, Krystof, Kantorová 2001;UN 2003) in line with the observation that it is a pan-European, trans-cultural phenomenon that spreads from northwest to southeast of the continent (Van de Kaa 2002). In spite of doubts about applicability of the concept of second demographic transition to Balkan countries due to their specific socio-cultural matrix in relation to that in western societies, macro-level evidence suggests that Serbia excluding Kosovo started to follow the tempo of second demographic transition in southeastern Europe after the stagnation in the 1990s (Bobić, Vukelić 2011). If drivers of second demographic transition, in terms of individual change of value orientations (Lesthaeghe 2010b), are in work, recognized sociocultural differences among subregions of the country should explain existence of spatial differentiation in demographic development produced by different tempo in accepting ideational changes.…”
Section: Introductionmentioning
confidence: 99%